Intra‐arterial combination therapy for experimental acute ischemic stroke - Michael E. Maniskas; Jill M. Roberts; Amanda Gorman; Gregory J. Bix; Justin F. Fraser (Wiley, 2022)
Abstract Acute ischemic stroke continues to devastate millions of individuals worldwide. Current treatments work to restore blood flow but not rescue affected tissue. Our goal was to develop a combination of neuroprotective agents administered intra‐arterially following recanalization to target ischemic tissue. Using C57Bl/6J male mice, we performed tandem transient ipsilateral middle cerebral/common carotid artery occlusion, followed by immediate intra‐arterial pharmacotherapy administration through a standardized protocol. Two pharmacotherapy agents, verapamil and lubeluzole, were selected based on their potential to modulate different aspects of the ischemic cascade; verapamil, a calcium channel blocker, works in an acute fashion blocking L‐type calcium channels, whereas lubeluzole, an N‐methyl‐D‐aspartate modulator, works in a delayed fashion blocking intracellular glutamate trafficking. We hypothesized that combination therapy would provide complimentary and potentially synergistic benefit treating brain tissue undergoing various stages of injury. Physiological measurements for heart rate and pulse distention (blood pressure) demonstrated no detrimental effects between groups, suggesting that the combination drug administration is safe. Tissue analysis demonstrated a significant difference between combination and control (saline) groups in infarct volume, neuronal health, and astrogliosis. Although a significant difference in functional outcome was not observed, we did note that the combination treatment group had a greater percent change from baseline in forced motor movement as compared with controls. This study demonstrates the safety and feasibility of intra‐arterial combination therapy following successful recanalization and warrants further study.